2014
DOI: 10.1371/journal.pone.0087327
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fatty Acid Oxidation in Mouse Cumulus-Oocyte Complexes during Maturation and Modulation by PPAR Agonists

Abstract: Fatty acid oxidation is an important energy source for the oocyte; however, little is known about how this metabolic pathway is regulated in cumulus-oocyte complexes. Analysis of genes involved in fatty acid oxidation showed that many are regulated by the luteinizing hormone surge during in vivo maturation, including acyl-CoA synthetases, carnitine transporters, acyl-CoA dehydrogenases and acetyl-CoA transferase, but that many are dysregulated when cumulus-oocyte complexes are matured under in vitro maturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 63 publications
5
91
0
1
Order By: Relevance
“…This hypothesis is supported by recent reports in mouse COC where expression of genes involved in FAO were altered after FAO inhibition (Brisard et al 2014). Abundance of genes involved in FAO is also increased in COC after treatment with rosiglitazone, an agent known to inhibit FAO (Dunning et al 2014). Similar to the observed increase in Cpt2 transcripts in cumulus cells after maturation with low levels of palmitic acid, with or without carnitine, an increase in Cpt1 has been documented in pancreatic cell lines when palmitate, oleate, and linoleate are supplied (AssimacopoulosJeannet et al 1997).…”
Section: Discussionsupporting
confidence: 74%
“…This hypothesis is supported by recent reports in mouse COC where expression of genes involved in FAO were altered after FAO inhibition (Brisard et al 2014). Abundance of genes involved in FAO is also increased in COC after treatment with rosiglitazone, an agent known to inhibit FAO (Dunning et al 2014). Similar to the observed increase in Cpt2 transcripts in cumulus cells after maturation with low levels of palmitic acid, with or without carnitine, an increase in Cpt1 has been documented in pancreatic cell lines when palmitate, oleate, and linoleate are supplied (AssimacopoulosJeannet et al 1997).…”
Section: Discussionsupporting
confidence: 74%
“…During ovulation, the maturing oocyte increases energy use through mitochondrial oxidation of free fatty acids (FFAs) as a more efficient source of ATP than glycolysis (67)(68)(69). FFAs within the COC, either taken up from follicular fluid or broken down from cellular lipid, enter mitochondria to undergo conversion into acetyl CoA, which enters the TCA to produce ATP through beta-oxidation ( Fig.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…In porcine oocytes, levels of ACSL3 and ACADL, which activate long-chain fatty acids before their entry into mitochondria and catalyse the first step in the b-oxidation spiral respectively, were found to be dysregulated in another model of poor oocyte developmental competence (Yuan et al 2011). Recently we have found that mouse COCs matured in vitro metabolise fatty acid at less than half the rate of COCs matured in vivo, in association with dysregulated expression of at least 15 genes involved in fatty acid activation, transport and oxidation (Dunning et al 2014).…”
Section: Metabolism Of Fatty Acids For the Production Of Atpmentioning
confidence: 99%